Variables Determining For Impairment On Productive Assets In Islamic Banks In Indonesia - nihayah, ana zahrotun; Rifqi, Lathif Hanaifr (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
AbstractPurpose - This study aims to examine the effect of profit, productive assets, financing and problem financing on impairment on productive assets on Islamic banks in Indonesia.Method - Data used are secondary data obtained from the Islamic Banking Statistics report for the 2015-2019 period. The sample used in this study was 12 Islamic Commercial Banks and data processing using SPSS 25.0 software.Result - The results of this study indicate that the variable earning assets, financing and problem financing have a significant effect on the impairment on productive assets variable, while the profit variable does not have a significant effect on Impairment on productive assets variable.Implication - This study can be used as a reference by Islamic banks in determining the amount of Impairment on productive assets.Originality - This study analyzes the determinants of Impairment on productive assets at Islamic Banks.